Internet as a source of information in public health. Part I. The origin and history of Internet - Bryła, Marek; Stegienta, Grzegorz; Maniecka-Bryła, Irena (Polish Journal of Public Health, 2009)
The paper deals with Internet as a modern source of academic information used, inter alia, in public health. The introduction illustrates possible applications of Internet services. The origin of the word “Internet” is explained and its defi nition provided. Then we focus on the origin and history of the Internet. We present the most important events in the history of this electronic medium and of people who make the greatest contribution to its development, The greatest milestone in the development of Internet took place in 1991, when Tim Berners-Lee created a prototype of the www (World Wide Web) system in order to share quickly and easily his research results with other specialists. The www enabled to put hypothesis in documents, which made it possible to combine documents by various authors into a single entity. In order to explore such documents on the Internet, Tim Berners-Lee created the fi rst Internet text browser called «WorldWideWeb». Special attention should also be drawn to the launch of the Google browser in 1997 which has facilitated getting information. We emphasise the signifi cant role of Paul Baran, a scientist of Polish origin, in the development of the technique of data transfer. His visions concerning new direction of computer use were implemented many years after having been proposed. The development of the Internet is very dynamic: it is estimated that the number of the Internet users increased from 50 million to 1.5 billion in the period 1997-2008.